PENGARUH PERBEDAAN CAMSHAFT STANDAR DAN CAMSHAFT AFTERMARKET TERHADAP DAYA DAN TORSI PADA SEPEDA MOTOR YAMAHA JUPITER 110 CC - Anam, Khoirul; Prasetyo, Imam; Irfan Setiawan, Muhammad (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2019)
One of the efforts to produce a motorcycle with high performance is by making modofications to the camshaft. Because they are not satisfied with the manufacturer’s standard camshaft and aim to increase power and torque using the dynotest test method on a Yamaha Jupiter 110 cc motorcycle, one way is to replace it with an aftermarket camshaft that has a higher lift. The standard is 4,5 mm and the aftermarket camshaft has a 5mm lift it makes more fuel intake and more power..Based on the test result, it is found that using aftermarket camshaft can increase the power and torque for maximum power result on a standard camshaft of 6,7 hp at 5660 rpm engine speed and 10,34 Nm of torque at 2819 rpm engine speed then aftermarket camshaft produce 7,6 hp at engine speed. 6087 rpm engine speed and 10,66 Nm of torque at 2765 rpm engine speed.Keywords : Camshaft, power, and Torque